2014
DOI: 10.1016/s1995-7645(14)60228-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on phytochemical evaluation and antimicrobial activity of Borassus flabellifer Linn against some human pathogens

Abstract: B. flabellifer exhibited higher rate of growth inhibition against some human pathogens, so it can be used for treatment of some infectious diseases. Further studies are being carried out to separate and purify the individual compounds that are present in seed coat of B. flabellifer by using various chromatographic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…B.subtilis showed the maximum zone of inhibition of 18 mm, 24 mm and 26 mm at all the concentrations of 50 μg ml −1 , 100 μg ml −1 , 500 μg ml −1 respectively. This is in agreement to the previous literature where the extract alone showed highest activity against B.subtilis [28]. The larger zone of inhibition can be accredited to the synergistic activity of the iron oxide nanoparticles and the phytocomponents 50 14 11 17 18 9 9 100 20 18 19 24 11 10 500 23 20 22 26 15 13 coated on the nanoparticles [48].…”
Section: Antimicrobial Activity Using Agar Well Diffusionsupporting
confidence: 92%
See 2 more Smart Citations
“…B.subtilis showed the maximum zone of inhibition of 18 mm, 24 mm and 26 mm at all the concentrations of 50 μg ml −1 , 100 μg ml −1 , 500 μg ml −1 respectively. This is in agreement to the previous literature where the extract alone showed highest activity against B.subtilis [28]. The larger zone of inhibition can be accredited to the synergistic activity of the iron oxide nanoparticles and the phytocomponents 50 14 11 17 18 9 9 100 20 18 19 24 11 10 500 23 20 22 26 15 13 coated on the nanoparticles [48].…”
Section: Antimicrobial Activity Using Agar Well Diffusionsupporting
confidence: 92%
“…Similar results for the presence of elemental composition from the extract have already been reported [47]. The phytochemical constituents in the seed coat extract have been screened for the presence of tannins, flavanoids, saponins, terpenoids, glycosides [28], whereas further investigation needs to be done in order to determine the elemental composition of the seed coat extract.…”
Section: Morphological and Elemental Analysissupporting
confidence: 74%
See 1 more Smart Citation
“…Wongmanit et al reported the antibacterial activity of B. flabellifer male flower ethanolic extract against Enterococcus faecalis and Staphylococcus aureus , but did not report the activity against Escherichia coli [ 22 ]. Alamelumangai et al reported that the methanolic and ethanolic seed coat of B. flabellifer extract at 50 mg/mL could inhibit the growth of Aspergillus brasiliensis and Bacillus subtilis [ 26 ]. Reshma et al isolated 2,3,4-trihydroxy-5-methylacetophenone from palm juice extract, which showed a broad-spectrum antibacterial activity against Escherichia coli, Mycobacterium smegmatis, Staphylococcus aureus, and Staphylococcus simulans [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…18 Methanolic, ethanolic and aqueous seed extracts have antimicrobial activity. 19 Alcoholic root extract has hypoglycaemic activity 20 and methanolic leaves extract has anthelmintic activity. 21 Ethanolic flower extract has also been reported for anti-inflammatory activity, 22 ethanolic and aqueous seed extracts have diuretic activity, 23 whilst aqueous fruit extract has wound healing activity.…”
Section: Introductionmentioning
confidence: 99%